Moderating effect of slack resources on the charitable giving and firm performance nexus - Tan, Siow-Hooi; Muzafar Shah Habibullah,; Ong, Hway-Boon; Azali Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to examine the relationship between charitable giving (CG) and firm performance (FP) of tourism-related firms across various economic regions. Panel data on tourism-related firms covering the years 2002 to 2014 are utilised. Results generating from the system-GMM estimator reveals an inverse U-shaped relationship between CG and FP. This curvilinear relationship suggests that though CG enhances FP, it does not imply an unlimited increased in charitable giving. Beyond a certain limit, firm performance will deteriorate. Furthermore, the empirical results also suggest that a firm’s slack resources play a vital role in strengthening the CG-FP relationship. This finding implies that firms with higher flexibility of slack resources may allocate their slack resources in relation to CG to improve their financial performance and subsequently remain competitive in the industry.